NURSING CARE FOR PATIENTS WITH HUMAN IMMUNODEFICIENCY - HIV - Pereira Nunes, Adenilson; Lívia Silva Fonseca Moreira de Medeiro, Renata; Gonçalves Leoncio Batista, Aurélia; Rodrigues Feliciano, Lucyo; Eveny de Abreu , Jaddy (Health and Society, 2024)
INTRODUCTION: The presence of the human immunodeficiency virus (HIV) triggers several consequences in the life of the carrier. Adequate treatment allows complications to be alleviated, including Acquired Immunodeficiency (AIDS), which benefits the patient. OBJECTIVE: To present the importance of nursing care for people with the human immunodeficiency virus (HIV). METHODOLOGY: The work developed is a literature review study. A search was carried out in the SCIELO and BVS databases, published between 2018 and 2023. 13 articles were selected that met the inclusion criteria in Portuguese, English and Spanish. This study identified activities related to nursing care and assistance for patients with human immunodeficiency. RESULTS AND DISCUSSION: The work of this professional covers this disease, in addition to providing safety, technical skills and training to intervene in the process of both infection and disease, making it clear that these professionals explain current knowledge, which when implemented in their daily practice In screenings related to sexually transmitted infections, great competence and completeness are observed for patients who have human immunodeficiency, as well as acquired immunodeficiency. CONCLUSION: In short, the importance of nursing professionals in treating people with the human immunodeficiency virus (HIV) was noted. Nursing professionals promote an improvement in the lives of sufferers, through rehabilitation actions and encouragement of self-care.